The Effect of Gratitude on Social Comparison Among Emerging Adulthood TikTok Users in Padang City - Khairunnisa, Aisha Nabila; Damra, Hanny Rufaidah; Akbar, Amin (INDONESIAN COUNSELING AND PSYCHOLOGY, 2026)
The rapid growth of social media use, particularly TikTok, has increased individuals’ exposure to curated representations of others’ lives, which may intensify social comparison processes. This study aims to examine the effect of gratitude on social comparison among emerging adulthood TikTok users in Padang City. A quantitative approach with a simple linear regression design was employed. The participants consisted of 235 emerging adults aged 18–25 years who actively use TikTok, selected through convenience sampling. Data were collected using standardized measurement scales of gratitude and social comparison. Statistical analysis was conducted using SPSS 25. The results revealed that gratitude has a negative and significant effect on social comparison (β = -0.331; p = 0.000), with a contribution of 10.9% (R² = 0.109). These findings indicate that individuals with higher levels of gratitude tend to engage less in social comparison. This study highlights the role of gratitude as a protective psychological factor in mitigating the negative impact of social media use and suggests that fostering gratitude may support healthier self-evaluation processes among emerging adults in digital environment.